Food safety practice and associated factors among food handlers working in food and drinking establishments in Debre Birhan City, North Eastern Ethiopia: A convergent parallel mixed-method study - Belachew Tekleyohannes Wogayehu (PLoS ONE, 2026)
Background Food-borne illnesses pose a major global public health threat, affecting up to 30% of people annually in higher-income countries and contributing to hundreds of thousands of deaths each year with the heaviest burden falling on low and middle income countries. In Ethiopia, prior research on food handlers’ safety practices has been limited to quantitative methods offering little insight into cultural, behavioral and institutional barriers. To the best of our knowledge, limited mixed-methods evidence exists in this context. Therefore, this mixed-methods study addresses the gap through providing comprehensive evidence from North Eastern Ethiopia on factors influencing food safety practices. Objective This study aims to assess food safety practices and associated factors among food handlers working in food and drinking establishments in Debre Birhan city, North Eastern Ethiopia. Methods A convergent-parallel mixed-methods study with a cross-sectional quantitative strand was conducted from January 10 to February 28, 2025, among 415 randomly selected food handlers in Debre Birhan city, North Eastern Ethiopia. Quantitative data were collected using a pre-tested structured questionnaire and observation method and analyzed using STATA version 14. Multivariable binary logistic regression with 95% confidence intervals and a p-value ≤ 0.05 was used to identify factors associated with food safety practices. Qualitative data were analyzed using ATLAS.ti version 8 software. Results The magnitude of poor food safety practices among food handlers was 72%. Educational status (AOR = 3.2; 1.206–5.337), working ≤ 2 years (AOR = 2.7; 1.026–4.009), lack of food safety training (AOR = 4.3; 1.997–7.820) and poor knowledge (AOR = 3.9; 1.853–6.983) were statistically associated with poor food safety practice among food handlers. Lack of food safety training, poor risk perception, weak enforcement, lack of standardized guidelines, inadequate facilities and insufficient equipment were identified as barriers for good food safety practice. Conclusions Food safety practice among food handlers in the current study was low. Quantitative findings showed that educational status, working ≤ 2 years, lack of food safety training and poor knowledge were factors statistically associated with poor food safety practice. Qualitative findings provided limited access to training, poor risk perception, weak enforcement, lack of standardized guidelines, inadequate equipment and facilities jointly undermine food safety compliance. Addressing these factors particularly through enhanced training and knowledge improvement as well as regular and supportive supervisory, monitoring and evaluation mechanisms could substantially improve adherence to safe food handling and reduce the risk of foodborne diseases.